2019
DOI: 10.1002/asia.201900176
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Alkylarylation of Unactivated Alkenes: Synthesis of 3‐Alkyl Indolines from N‐Allyl Anilines and Alkanes

Abstract: Ar are example of C(sp 3 )ÀHf unctionalization of simple alkanes with unactivated alkenes is presented.I n the presence of ac opper salt and di-tert-butyl peroxide (DTBP), N-allyl anilinesu nderwent exo-selective alkylation/ cyclization cascade with unactivated alkenic bonds as radical acceptors and simple alkanes as radicalp recursors, providing ad irect access to 3-alkyl indolines.T he present protocol features simple operation, broad substrate scope and great exo selectivity.Alkanesa re principalc onstituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…On the basis of previous reports 9 b,i , m ,16–25 and above experimental results, a possible mechanism was proposed and is depicted in Scheme 3. In the beginning, the thermal decomposition of DTBP leads to the formation of the t -butoxyl radical which can generate methyl radicals by a β-cleavage pathway.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the basis of previous reports 9 b,i , m ,16–25 and above experimental results, a possible mechanism was proposed and is depicted in Scheme 3. In the beginning, the thermal decomposition of DTBP leads to the formation of the t -butoxyl radical which can generate methyl radicals by a β-cleavage pathway.…”
Section: Introductionmentioning
confidence: 92%
“…For example, acetonitrile (CH 3 CN), azodiisobutyrodinitrile (AIBN), cyclohexane, benzaldehyde, tetrahydrofuran (THF), toluene, acetone, perfluorobutyl iodide ( n -C 4 F 9 I), dimethyl phosphite (HPO(OMe) 2 ) and trifluoromethylating agents have been used as the radical precursor to construct indoline structures in recent years. 16–25 Although remarkable efforts have been made in this field, the silylarylation of unactivated alkenes for the synthesis of 3-silyl indolines has not been studied. As part of our continuous studies on C–H functionalization 26 and organosilicon chemistry, 27 herein, we report the silylation of unactivated alkenes with silanes through a free-radical cascade process to construct 3-silyl indoline compounds (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that even the readily oxidized formyl group was well tolerated and this strategy was also suitable for thioether. In the same year, Liang's group 42 reported another example of C(sp 3 )–H oxidative functionalization of cyclohexane. 3-Alkyl indolines could be obtained using N -allyl anilines and cyclohexane in the presence of di-tert -butyl peroxide (DTBP) and copper salt, providing a novel approach to 3-alkyl-2-unsubstituted indolines from acyclic materials.…”
Section: Intermolecular Cyclization Initiated By Directed C(sp3)–h Ox...mentioning
confidence: 99%
“…In 2019, Liang and co-workers reported an exo-selective alkylation/cyclization cascade in the presence of CuI (Scheme 21). 30 N-Allylanilines with unactivated alkenic bonds were used as radical acceptors and simple alkanes as radical precursors enabling direct access to 2-unsubstituted 3-alkylindolines. This protocol is simple operation and has broad substrate scope and great exo-selectivity.…”
Section: Scheme 20 Proposed Mechanismmentioning
confidence: 99%